Training time and quality of smartphone-based anterior segment screening in rural India - Ludwig CA (Dove Medical Press, 2017)
Cassie A Ludwig,1 Megan Newsom,1 Alexandre Jais,1 David J Myung,1,2 Somasheila I Murthy,3 Robert T Chang1 1Department of Ophthalmology, The Byers Eye Institute, Stanford University School of Medicine, 2Department of Ophthalmology, VA Palo Alto Health Care System, Palo Alto, CA, USA; 3Cornea and Anterior Segment Service, L V Prasad Eye Institute, Kallam Anji Reddy Campus, Hyderabad, India Objective: We aimed at evaluating the ability of individuals without ophthalmologic training to quickly capture high-quality images of the cornea by using a smartphone and low-cost anterior segment imaging adapter (the “EyeGo” prototype). Methods: Seven volunteers photographed 1,502 anterior segments from 751 high school students in Varni, India, by using an iPhone 5S with an attached EyeGo adapter. Primary outcome measures were median photograph quality of the cornea and anterior segment of the eye (validated Fundus Photography vs Ophthalmoscopy Trial Outcomes in the Emergency Department [FOTO-ED] study; 1–5 scale; 5, best) and the time required to take each photograph. Volunteers were surveyed on their familiarity with using a smartphone (1–5 scale; 5, very comfortable) and comfort in assessing problems with the eye (1–5 scale; 5, very comfortable). Binomial logistic regression was performed using image quality (low quality: <4; high quality: ≥4) as the dependent variable and age, comfort using a smartphone, and comfort in assessing problems with the eye as independent variables. Results: Six of the seven volunteers captured high-quality (median ≥4/5) images with a median time of ≤25 seconds per eye for all the eyes screened. Four of the seven volunteers demonstrated significant reductions in time to acquire photographs (P1=0.01, P5=0.01, P6=0.01, and P7=0.01), and three of the seven volunteers demonstrated significant improvements in the quality of photographs between the first 100 and last 100 eyes screened (P1<0.001, P2<0.001, and P6<0.01). Self-reported comfort using a smartphone (odds ratio [OR] =1.25; 95% CI =1.13 to 1.39) and self-reported comfort diagnosing eye conditions (OR =1.17; 95% CI =1.07 to 1.29) were significantly associated with an ability to take a high-quality image (≥4/5). There was a nonsignificant association between younger age and ability to take a high-quality image. Conclusion: Individuals without ophthalmic training were able to quickly capture a high-quality magnified view of the anterior segment of the eye by using a smartphone with an attached imaging adapter. Keywords: EyeGo, macrolens, screening, usability, smartphone, adapter, paxos, healthy scholars